Factors Effecting Holding Period Of Construction Material Company Stocks In Indonesia - Shara, Fauziah; Harianti, Ati (Journal of Accounting Inaba, 2024)
This study aims to examine the influence of bid-ask spread, market value, stock price, and return variance on the holding period. The research employs a quantitative method. The data used is secondary data sourced from the financial reports of construction material companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2022. Data collection was conducted using a purposive sampling method, resulting in a selected sample of 144. This study was tested using panel data regression analysis techniques. The result shows the p-values for market value, stock price, and return variance are each below the significant level of 0.05, indicating that these variables have a statistically significant impact on the holding period of stocks. Both market value and return variance show a negative relationship with the holding period. Additionally, the F-Statistic value exceeds the critical value from the F-distribution (f-table), suggesting that bid ask spread, market value, stock price, and return variance collectively have a significant influence on the holding period of company stocks.